Elemental Composition of Natural Nanoparticles and Fine Colloids in European Forest Stream Waters and Their Role as Phosphorus Carriers. Issue 10 (26th October 2017) - Gottselig, N.; Amelung, W.; Kirchner, J. W.; Bol, R.; Eugster, W.; Granger, S. J.; Hernández‐Crespo, C.; Herrmann, F.; Keizer, J. J.; Korkiakoski, M.; Laudon, H.; Lehner, I.; et al.
Abstract: Biogeochemical cycling of elements largely occurs in dissolved state, but many elements may also be bound to natural nanoparticles (NNP, 1–100 nm) and fine colloids (100–450 nm). We examined the hypothesis that the size and composition of stream water NNP and colloids vary systematically across Europe. To test this hypothesis, 96 stream water samples were simultaneously collected in 26 forested headwater catchments along two transects across Europe. Three size fractions ( 1–20 nm, >20–60 nm, and >60 nm) of NNP and fine colloids were identified with Field Flow Fractionation coupled to inductively coupled plasma mass spectrometry and an organic carbon detector. The results showed that NNP and fine colloids constituted between 2 ± 5% (Si) and 53 ± 21% (Fe; mean ± SD) of total element concentrations, indicating a substantial contribution of particles to element transport in these European streams, especially for P and Fe. The particulate contents of Fe, Al, and organic C were correlated to their total element concentrations, but those of particulate Si, Mn, P, and Ca were not. The fine colloidal fractions >60 nm were dominated by clay minerals across all sites. The resulting element patterns of NNP <60 nm changed from North to South Europe from Fe‐ to Ca‐dominated particles, along with associated changes in acidity, forest type, and dominant lithology. Key Points: Stream phosphorus is largely bound to natural nanoparticles and colloids The chemical composition of colloids varies systematically from Northern to Southern European streams